25-hydroxycholesterol effect on membrane structure and mechanical properties - Domingues, Marco (2021)
© 2021 by the authors. Licensee MDPI, Basel, Switzerland. This article is an open access article distributed under the terms and conditions of the Creative Commons Attribution (CC BY) license (http://creativecommons.org/licenses/by/4.0/).